2011
DOI: 10.1530/eje-11-0539
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced GH secretion in the assessment of GH deficiency in adult individuals

Abstract: Objective: The role of exercise testing in the assessment of GH deficiency (GHD) in adult patients is currently unclear. This study aimed at evaluating the diagnostic value of exercise-induced GH levels in the detection of severe GHD in adult patients. Methods: Fourteen patients confirmed to have severe GHD according to current guidelines and 20 healthy control individuals (CI) exercised for 120 min at 50-60% of their individual VO2 max . GH was measured before and every 30 min throughout exercise. The diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…While we have recently shown that a standardized aerobic exercise of moderate intensity but longer duration is a reliable test in predicting severe GHD in adult individuals (Zueger et al 2011), the present study provides evidence that an excellent accuracy can also be obtained using a shorter test protocol albeit with higher exercise intensity.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…While we have recently shown that a standardized aerobic exercise of moderate intensity but longer duration is a reliable test in predicting severe GHD in adult individuals (Zueger et al 2011), the present study provides evidence that an excellent accuracy can also be obtained using a shorter test protocol albeit with higher exercise intensity.…”
Section: Discussionsupporting
confidence: 49%
“…Although GHD may be regarded a comparably rare disease, its frequency may be considerably higher in specialized referral centers (Zueger et al 2011) and reliable tests for GHD are, therefore, important to identify individuals that may potentially benefit from GH replacement therapy. The insulin tolerance test is considered to be one of the gold standards in assessing the integrity of the GH axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy subjects exercise induces a strong GH secretion [17]. In patients suffering from GHD such an exercise induced GH-response is lacking [31,32]. Since GH is known to have a strong lipolytic effect [23] we speculate that lipolysis may also be reduced during exercise in patients with GHD compared to healthy individuals.…”
mentioning
confidence: 99%